Hot Spot Offset Variability from Magnetohydrodynamical Thermoresistive Instability in Hot Jupiters - Raphaël Hardy; Paul Charbonneau; Andrew Cumming (The Astrophysical Journal)
Hot Jupiter (HJ) atmospheres are possibly subject to a thermoresistive instability (TRI). Such an instability may develop as the ohmic heating increases the electrical conductivity in a positive feedback loop, which ultimately leads to a runaway of the atmospheric temperature. We extend our previous axisymmetric one-dimensional radial model, by representing the temperature and magnetic diffusivity as a first-order Fourier expansion in longitude. This allows us to predict the hot spot offset during the rapid unfolding of the TRI and following Alfvénic oscillations. The instability is periodically triggered and damped within ≈10–40 days, depending on the magnetic field strength, with months of slow buildup between recurring bursts. We show a few representative simulations undergoing TRI, in which the peak flux offset varies between approximately ±60 ^∘ on a timescale of a few days with potentially observable brightness variations. Therefore, this TRI could be an observable feature of HJs, given the right timing of observation and transit and the right planetary parameters.